The Difference Plaque Index of Brushing Teeth A Combination to Grade Students - Yessi Yuzar; Lisnayetti Lisnayetti; Nurul Amelia (Jurnal Kesehatan Masyarakat Andalas, 2017)
Plaque is caused of the caries and periodontal deseases. Plaque can be cleaned up by mechanization that is brushing teeth. The data show that decline in behave right of brushing teeth from 6.2% in 2007 become 1.7% in 2013. Best on the kinds of the movement of tooth brusing, there are six methode. Every techniques of brushing teeth having a overbalance and shortage. The objective research is knowing the differences plaque index of brushing teeth a combination of techniques roll and horizontal with a combination techniques vertical and horizontal to grade IV – V students in SDN 08 Kubang Duo Koto Panjang. The methode research is quasi experiment with pretest and postest approach. Technique sampling is random sampling as many as 54 people. Data retrival through observation dan treatment. The analysis data statistic with T-Test showed the significant difference between plaque index of brushing teeth a combination of techniques roll and horizontal with a combination techniques vertical and horizontal with p value 0,03. A combination of techniques roll and horizontal is more effectivly lowering plaque. Suggestion for the students to apply tooth brushing a combination of techniques roll and horizontal routinely every day 2 times to prevent the oral deseases.